Colombia : Technical Assistance Report-Reforming Energy Pricing. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2019)
This paper on Colombia focuses on reforming energy pricing. Rising fiscal challenges in Colombia can risk derailing the government from their commitment to meet both its headline deficit target of 2.4 percent in 2019 and its structural deficit target by 2022, under the existing fiscal rule. The government is committed to embark on a reform strategy that aims at safeguarding the fiscal framework. Energy subsidy reform is one element of the government's strategy to address fiscal pressures. Carefully designed reforms entail a gradual phasing out of subsidies in the case of fuel products and, in the case of electricity, an improvement in the targeting over the medium term. Illustrative simulations presented in this report highlight the fiscal and distributional impacts of different reform options. Simulations show that net fiscal gains could be achieved both for electricity and fuel products, while reducing distortions. The mission identified reform options to reduce energy subsidies while at the same time improve their targeting. The approach differs across sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet